Maternal dietary patterns associated with bone density in Chinese lactating women and infants at 6 months postpartum: a prospective study using data from 2018-2019 - Yalin Zhou; Xiaoyu Zhu; Ying Lü; Runlong Zhao; Hanxu Shi; Wanyun Ye; Zhang Wen; Rui Li; Hanming Huang; Yajun Xu (Food Science and Human Wellness)
This cohort study was designed to explore the relationship between maternal dietary patterns (DPs) and bone health in Chinese lactating mothers and infants. We recruited 150 lactating women at 1-month postpartum. The estimated bone mineral density (eBMD) of subjects’ calcanei and the information on dietary intake were collected. After 5-month follow-up, the eBMD of mothers and their infants were measured again. Factor analysis was applied to determine maternal DPs. General linear models were used to evaluate the association between maternal DPs and maternal eBMD loss or infants’ eBMD. With all potential covariates adjusted, Factor 2 (high intake of whole grains, tubers, mixed beans, soybeans and soybean products, seaweeds, and nuts) showed a positive association with the changes of maternal eBMD (β=0.16, 95% CI: 0.005, 0.310). Factor 3 (high intake of soft drinks, fried foods, and puffed foods) was inversely correlated with the changes of maternal eBMD (β=-0.22, 95% CI: -0.44, 0.00). The changes of maternal eBMD were positively associated with 6-month infants’ eBMD (β=0.34, 95% CI: 0.017, 0.652). In conclusion, Factor 2 might contribute to the maintenance of eBMD in lactating women, while Factor 3 could exacerbate maternal eBMD loss. Additionally, the changes of maternal eBMD presented a positive correlation with 6-month infants’ eBMD.